ENHANCING BANYUMARO RIVER TUBING TOURISM WITH MERCHANDISE DESIGN - Kusumawati, Yudhistya Ayu; Bhekti Setyo Wibowo; Frederik Masri Gasa; Hamzah Ramadhan (Bina Nusantara University, 2026)
Tourism is an important aspect as part of the government's priority. This paper investigates the enhancement of Banyumaro River Tubing tourism through innovative merchandise design, aiming to improve the overall visitor experience while promoting local culture and environmental awareness. The study begins by analyzing the current state of tubing tourism along the Banyumaro River Tubing, identifying the existing challenges related to visitor engagement, local economic benefits, and ecological sustainability. By integrating merchandise that reflects the unique attributes of the Banyumaro River Tubing and surrounding communities, the research underscores the potential for merchandise to serve not only as souvenirs but also as educational tools that raise awareness about river conservation and promote the local culture. Furthermore, the study employs design thinking to gain insights from local stakeholders. Results indicate that well-designed merchandise can significantly enhance brand recognition and visitor satisfaction, leading to increased repeat visits and a stronger economic impact on the local community. The findings offer actionable recommendations for local entrepreneurs and tourism operators on effective merchandise design strategies that align with sustainable tourism practices. This research contributes to the growing body of literature on tourism enhancement through product innovation, highlighting the role of local merchandise in driving sustainable tourism development in riverine environments.